1933
DOI: 10.2105/ajph.23.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacteriological Methods of Testing and Means of Disinfecting Water with Chlorine

Abstract: INCE the adoption of continuous feed chlorination of swimming pool water whereby residual chlorine contents of 0.2 to 0.5 p.p.m. may be maintained irrespective of the bathing load, bacterial quality comparable to drinking water has been obtained. In 1926, Stovall, Nichols, and Vincent 1 reported that the relationship between the bacterial purity of the water and the residual chlorine content as measured by the orthotolidine test was so satisfactory that this test could be depended upon as a measurement of sani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1933
1933
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…of 3 % solution per 170 ml. sample) to neutralize chlorine residues in water samples (Mallman & Cary, 1933 Reports on the toxic nature of sodium thiosulphate against, in particular, staphylococci (Kayser & van der Ploeg, 1965;Gross, Cofone & Huff, 1973) agree with unpublished results from this laboratory. The degree of inhibition will vary in different basal media.…”
Section: Sodium Thiosulphatesupporting
confidence: 80%
“…of 3 % solution per 170 ml. sample) to neutralize chlorine residues in water samples (Mallman & Cary, 1933 Reports on the toxic nature of sodium thiosulphate against, in particular, staphylococci (Kayser & van der Ploeg, 1965;Gross, Cofone & Huff, 1973) agree with unpublished results from this laboratory. The degree of inhibition will vary in different basal media.…”
Section: Sodium Thiosulphatesupporting
confidence: 80%
“…Notwithstanding public pools, by 2007 the number of private swimming pools in the United States increased to 8.4 million . The disinfection of recreational pools has been practiced for many years, and is essential to prevent outbreaks of disease . Yet from a survey of public pools, a majority had management code violations that could lead to infectious disease .…”
Section: Introductionmentioning
confidence: 99%
“…MaIlman and Carey (19) found that with swimming pool waters the ortho-tolidine test does not closely follow the bacteriological relationship previously reported by Stovall, Nichols, and Vincent. Later MaIlman and Ardrey (20) reported that neither the starch-iodide nor the orthotolidine test gave accurate indications of relative germicidal activity of various concentrations of chlorine either in the presence or absence of organic matter.…”
Section: Bacteriological Significance Of Residual Chlorinementioning
confidence: 78%